Transcriptome analysis of three medicinal plants of the genus Polygonatum: identification of genes involved in polysaccharide and steroidal saponins biosynthesis - Lu, Jimei; Yao, Jinchen; Pu, Jingzhe; Wang, Duomei; Liu, Junling; Zhang, Yazhong; Zha, Liangping (Frontiers in Plant Science, 2023)
Polysaccharides and saponins are the main active components of Polygonati Rhizoma.Studying the molecular mechanism of their synthesis pathway is helpful to improve the content of active components at the molecular level. At present, transcriptome analysis of three Polygonatum species (Polygonatum sibiricum Red., Polygonatum cyrtonema Hua, Polygonatum kingianum Coll. et Hemsl.) has been reported, but no comparative study has been found on the transcriptome data of the three species.Transcriptome sequencing was performed on the rhizomes of three Polygonatum species based on high-throughput sequencing technology, and all transcripts were assembled. A total of 168,108 unigenes were generated after the removal of redundancy, of which 121,642 were annotated in seven databases. Through differential analysis and expression analysis of key enzyme genes in the synthesis pathway of three Polygonatum polysaccharides and steroidal saponins, 135 differentially expressed genes encoding 18 enzymes and 128 differentially expressed genes encoding 28 enzymes were identified, respectively. Numerous transcription factors are involved in the carbohydrate synthesis pathway. Quantitative real-time PCR was used to further verify the gene expression level. In this paper, we present a public transcriptome dataset of three medicinal plants of the genus Polygonatum, and analyze the key enzyme genes of polysaccharide and steroidal saponins synthesis pathway, which lays a foundation for improving the active component content of Polygonati Rhizoma by molecular means.